1981
DOI: 10.1007/bf01657826
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the thyroid in youth

Abstract: This is a review of 68 patients 20 years of age and younger with well‐differentiated carcinoma of the thyroid seen at the University of North Carolina Memorial Hospital and University of Iowa Hospital since 1935. These patients are included in the Thyroid Carcinoma Registry that provides continuing follow‐up of all patients with carcinoma of the thyroid at these 2 hospitals. The historical, clinical, laboratory, and surgical pathological findings in these 68 patients, their treatment, and survival are reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
8

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 23 publications
0
29
0
8
Order By: Relevance
“…Since 1970, several additional studies on thyroid neoplasms in children after external X-ray therapy have been published (Table 2). 31,[43][44][45][46][47][48][49][50] Other studies of thyroid carcinoma after different sources of radiation exposure have shown an increase in incidence predominantly in the adult population. Thus, among the hundreds of cases of thyroid carcinoma in atomic bomb survivors of Hiroshima and Nagasaki, we could only find a description of two tumors in ~hi1dren.l~ Seven thyroid neoplasms were documented in residents from the Marshall Islands who were exposed to radioiodines in fallout from the 1954 atmospheric nuclear tests.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1970, several additional studies on thyroid neoplasms in children after external X-ray therapy have been published (Table 2). 31,[43][44][45][46][47][48][49][50] Other studies of thyroid carcinoma after different sources of radiation exposure have shown an increase in incidence predominantly in the adult population. Thus, among the hundreds of cases of thyroid carcinoma in atomic bomb survivors of Hiroshima and Nagasaki, we could only find a description of two tumors in ~hi1dren.l~ Seven thyroid neoplasms were documented in residents from the Marshall Islands who were exposed to radioiodines in fallout from the 1954 atmospheric nuclear tests.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its rarity there have been few detailed studies of the change in incidence with age and sex in childhood, or any change in incidence with time. Studies of large series of thyroid cancer in young children have been largely confined to major tertiary referral centres and have usually concentrated on the clinical behaviour and treatment rather than pathology Rosvoll, 1961, 1970;Buckwalter et al. 1981;Schlumberger et al, 1987;Zimmerman et al, 1988;Harness et al, 1992;Samuel and Sharma, 1991).…”
mentioning
confidence: 99%
“…Eine radikale prophylaktische Neck dissection wird im Kindesalter abgelehnt [6]. Wegen der Neigung zum multifokalen Tumorwachstum und frühzeitiger Metastasierung ist eine modifizierte Neck dissection mit Schonung des N. accessorius, M. sternocleidomastoideus und der V. jugularis interna gerechtfertigt [38].…”
Section: Introductionunclassified
“…Sie machen ca. 8% aller Schilddrüsen-karzinome im Kindesalter aus [6]. Eine Lebensverlängerung ist nur durch eine radikale Thyreoidektomie erreichbar [27,28].…”
unclassified